Efficacy of proactive long‐term maintenance therapy of canine atopic dermatitis with 0.0584% hydrocortisone aceponate spray: a double‐blind placebo controlled pilot study. Issue 2 (25th January 2016) - Lourenço, Ana M.; Schmidt, Vanessa; São Braz, Berta; Nóbrega, Diana; Nunes, Telmo; Duarte‐Correia, José H.; Matias, Daniela; Maruhashi, Emi; Rème, Christophe A.; Nuttall, Tim
Abstract : Background: Long‐term remission between flares of canine atopic dermatitis (CAD) can be difficult to achieve. Therefore, additional strategic forms of treatment are needed in order to target flare prevention. The concept of proactive therapy is recommended in the European guidelines for the treatment of human atopic eczema. Objectives: To evaluate the efficacy of a proactive treatment regimen with a 0.0584% hydrocortisone aceponate (HCA) spray for CAD. Animals: Client‐owned dogs with spontaneous atopic dermatitis (AD) ( n = 41). Methods: This pilot study was conducted as a randomised, placebo‐controlled, double‐blinded clinical trial with an end‐point of treatment failure. Dogs were treated once daily to remission, then randomly assigned to receive either the HCA spray ( n = 21) or a placebo ( n = 20) spray on two consecutive days each week. All dogs were on appropriate flea control. No topical or systemic anti‐inflammatory or antimicrobial agents were permitted. Intention‐to‐treat analysis was used. Results: At Day 0, all the dogs were in remission or had mild AD based on their Canine Atopic Dermatitis Extent and Severity Index, version 3 (CADESI‐03) scores. The time to relapse was significantly higher in the HCA group (median 115 d; range 31–260 d) compared to the placebo group (median 33 d; range 15–61 d) ( P < 0.0001). No adverse events were attributable to the HCA spray. Four dogs were lost to follow‐up and four were withdrawn after receiving prohibited medication. Conclusions and clinical importance: These results indicate that proactive long‐term therapy of CAD with an HCA spray administered on two consecutive days each week is effective and well‐tolerated. Abstract : Background – Long‐term remission between flares of canine atopic dermatitis (CAD) can be difficult to achieve. Therefore, additional strategic forms of treatment are needed in order to target flare prevention. The concept of proactive therapy is recommended in the European guidelines for the treatment of human atopic eczema.Objectives – To evaluate the efficacy of a proactive treatment regimen with a 0.0584% hydrocortisone aceponate (HCA) spray for CAD.Conclusions and clinical importance – These results indicate that proactive long‐term therapy of CAD with a HCA spray administered on two consecutive days each week is effective and well‐tolerated.